2010
DOI: 10.1097/aco.0b013e32833e15b9
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic pain following craniotomy

Abstract: Acute and chronic pain following craniotomy is frequent and underrecognized. Several surgical and patient risk factors predispose patients to pain following neurosurgery. Further research is needed to determine the mechanisms, predictors, prevention and optimal treatment of acute and chronic pain following craniotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
103
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 67 publications
0
103
0
4
Order By: Relevance
“…Acute postcraniotomy headache appears to include components of site-of-injury and tension-type headaches [2] , [9]. We found that preoperative administration of just a single dose of the non-steroidal inflammatory agent diclofenac slightly reduced both the incidence and the severity of acute postcraniotomy headache.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Acute postcraniotomy headache appears to include components of site-of-injury and tension-type headaches [2] , [9]. We found that preoperative administration of just a single dose of the non-steroidal inflammatory agent diclofenac slightly reduced both the incidence and the severity of acute postcraniotomy headache.…”
Section: Discussionmentioning
confidence: 65%
“…Nociception, in turn, provokes central sensitization, windup, and activation of brain structures involved in pain perception [9]. Reducing the initial nociceptive stimulus may thus reduce post-procedural pain which is the basis for preemptive analgesia, a concept introduced by Wall in the late 1980's [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Occurrence of pain in the postoperative period after brain surgery is sometime overlooked [5,[10][11][12]. Prevention of this serious complication is mostly associated with appropriate perioperative management, including the use of local anesthetics for scalp block in the intraoperative period, and adequate nociceptive therapeutic regimen.…”
Section: Painmentioning
confidence: 99%